Risk Factors And Complications Of Perinatal Mortality In High-Risk Pregnancies: A Systematic Literature Review - Ega Oktavia; Vitri Dwi Lestari; Lenny Irmawaty Sirait; Lisa Triana Arlym; Vivi Silawati (Borneo Nursing Journal (BNJ), 2026)
Background: Perinatal mortality remains a major public health problem, particularly among women with high-risk pregnancies. Maternal, placental, infectious, and obstetric complications contribute significantly to stillbirth, early neonatal death, and other adverse neonatal outcomes. Objective: This study aimed to identify risk factors and complications associated with perinatal mortality in high-risk pregnancies. Methods: This study used a Systematic Literature Review (SLR) design following the PRISMA 2020 guidelines. The research question was developed using the PICOS framework, focusing on pregnant women with high-risk pregnancies, maternal and obstetric risk factors, and perinatal mortality outcomes. Literature searches were conducted in ProQuest, PubMed, SpringerLink, ScienceDirect, and Semantic Scholar between March and May 2026. Keywords included “high-risk pregnancy,” “perinatal mortality,” “stillbirth,” “early neonatal death,” “risk factors,” and “pregnancy complications,” combined using Boolean operators (“AND” and “OR”). Inclusion criteria were English-language full-text studies published between May 2025 and May 2026 using cohort, case-control, cross-sectional, prospective, or retrospective designs. Study selection followed the PRISMA flowchart through identification, screening, eligibility, and inclusion stages. From 21,401 identified articles, 14 studies met the eligibility criteria and were included in the review. Results: The reviewed studies showed that maternal COVID-19 infection, inherited thrombophilia, hypertensive disorders, placental dysfunction, maternal undernutrition, abnormal body mass index, advanced maternal age, and obstetric complications significantly increased the risk of stillbirth, preterm birth, fetal growth restriction, low birth weight, and neonatal death. Placental abnormalities and placental abruption were strongly associated with adverse neonatal outcomes. Specialized antenatal services, maternal risk stratification, thromboprophylaxis in selected patients, and planned birth at optimal gestational age were associated with improved maternal and neonatal outcomes. Conclusion: Perinatal mortality in high-risk pregnancies is influenced by multiple maternal and obstetric factors. Early identification, specialized antenatal care, and individualized management are essential to reduce preventable maternal and neonatal mortality.